Emerging Adults and Christian Faith: The Faith Experience of Emerging Adults in the Pacific Northwest - Drovdahl, Robert (Christian education journal, 2020)
A new life-cycle stage, emerging adulthood, has gained increasing traction. Since research shows intersectionality between life-cycle stage and religious experience, research is warranted on this question: How do emerging adults experience faith? This article provides background on emerging adulthood theory, summarizes research on religious life among emerging adults in the Pacific Northwest, and describes early findings of a Lilly Endowment study on emerging adults' experience of faith. It concludes by considering implications for ministry.